2006
DOI: 10.1080/09637480600802371
|View full text |Cite
|
Sign up to set email alerts
|

Honey ameliorates influence of hemorrhage and food restriction on renal and hepatic functions, and hematological and biochemical variables

Abstract: The objectives were to assess the effects of various diets, including total food restriction with 50% honey feeding, total food restriction with 50% dextrose feeding or adlibitum (control group) commercial regular diet, on the hematology and biochemical variables, and to assess the effects of the various diets on the influence of acute blood loss on the same parameters. Thirty Sprague-Dawley albino rats were divided into three groups, 10 rats each: group A, fed a commercial regular diet; group B, total food re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Furthermore, the scolicidal efficacy of propolis, which is a resinous material obtained by honey bees from plants or flowers, has been shown in cystic hydatid disease [19] . Recently, it has been found that honey leads to increased levels of NO in biological fluids and to reduced liver enzymes, such as AST and ALT, in blood [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the scolicidal efficacy of propolis, which is a resinous material obtained by honey bees from plants or flowers, has been shown in cystic hydatid disease [19] . Recently, it has been found that honey leads to increased levels of NO in biological fluids and to reduced liver enzymes, such as AST and ALT, in blood [20] .…”
Section: Discussionmentioning
confidence: 99%
“…However it is postulated that vitamins such as vitamins A, C and E, as well as flavonoids and phenolic acids [6][7][8][9]. Studies have demonstrated some beneficial effects of honey such as gastrointestinal [10,11] and reproductive protections [12], as well as hypoglycaemic [13], antihypertensive [7], antibacterial [14], antifungal [15], anti-inflammatory [16] and antioxidant [12,17] effects. Honey has been used as a traditional nutrient by local Malaysian population to enhance fertility and vitality.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that honey feeding during total food restriction has protective effects on both liver and kidney after acute blood loss [19]. In another experiment, we found that oral honey feeding significantly ameliorates biochemical and hematological changes obtained after CCl4 injection; showing hepato-renal protection [20].…”
Section: Figmentioning
confidence: 67%
“…We have found that honey has beneficial effects on renal function in normal volunteers [18]. In addition, our studies demonstrated that honey can protect liver and kidney during acute blood loss and after CCl4 intoxication [19][20][21]. Honey has been mentioned in Holey books as a healer of diseases.…”
Section: Introductionmentioning
confidence: 99%